Temporality and hope in pastoral care and counseling - Sathler-Rosa, Ronaldo (2010)
This essay examines the themes of temporality and hope from a pastoral-theological perspective. Following this section, it identifies some threats to hope in contemporary societies and some consequences of destruction of hope. Finally, this essay suggests aspects to take into account in terms of the construction of a pastoraltheological anthropology correlated to the discussed themes.